Oral health knowledge and practices of women attending dental clinics of Baghdad University - Al-Dafaai, Raya R.; Hoobi, Nibal M. (Journal of Baghdad College of Dentistry, 2019)
Background: Knowledge is considered to be essential for developing healthy practices and preventing the main oral diseases. In some developing countries, women were at higher risk to develop these diseases. This study was conducted to evaluate women’s dental knowledge and practices through a specific questionnaire and the relationship with patient’s educational level and the number of their children. Subjects and method: Women, aged from 25-35 years old, were selected to participate in the current study. They were attending dental clinics in the teaching hospital of Baghdad University. Each participant was instructed to answer questionnaire sheet which is previously prepared in Arabic language by the authors. The total number of women was divided into three groups according to women’s educational level and the number of their children. Results: The number of women that participated in the study was 150. Higher percent of them (58.7%) have received instruction on the use of dental floss but 60.0% had no information about fluoride. Dental floss was used by only 24.7% of women. Higher percent of women eat candies, chocolate bars and cookies in between meals. Significant association was reported between educational level and oral health information. Educational level didn’t influence patients’ health practices. Frequency of follow-up appointments and toothbrushes changes were higher among women with less number of children. Conclusion: The study revealed important gaps in oral health practices especially in diet control and the use of dental floss. There is a need for frequent dental educational programmes among women to promote the proper practices and to achieve good oral hygiene.